Organization as a Support System among Revert Clients in Malaysia - Samsiah, Jayos; Faizah, Abd Ghani; Lokman, Mohd Tahir; Kamarul Azmi, Jasmi; Nur Fatihah, Abdullah Bandar (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2017)
It is significant for the reverts to have an existing helping organization. Therefore, this study aims to identify organizational issues that are directly and indirectly involved with counsellors at the Council of Islamic Religious Department in Malaysia. This study utilizes a qualitative approach by using the case study method. This study involved five (5) counsellors from Council of Islamic Religious Department in Malaysia. This study used the N'Vivo 10.0 for the data analysis to develop themes and sub-themes that related to this study. The findings showed that there are two (2) sub themes involved both government and non-government. There are six (6) sub-sub themes for the government which are Jabatan Agama Islam, Jabatan Mufti, Pusat Dakwah Islamiah, Pusat Kaunseling MAINS Negeri Sembilan, Jabatan Kehakiman and Baitulmal. While, non-government has ten (10) sub-sub themes; Lembaga Kaunselor Malaysia, Unit Saudara Baru, Unit Ukhuwah, Pusat Saudara Baru Darul Saadah, Darul Ukhuwah Yayasan Kasih Sayang, Volunteer Body, Malaysian Chinese Muslim Association (MACMA), Pertubuhan Kebajikan Islam Malaysia (PERKIM), PERKAMA and Skuad Mubaligh Seremban. In conclusion, this study could be used as a guide for counsellors to provide guidance and counselling services to revert clients.